TAKE AND GIVE STRATEGY AS A CHARACTER EDUCATION MODEL TO REDUCE BULLYING IN AISYIYAH BUSTANUL ATHFAL KINDERGARTEN - Nur Anifauziah; Khotimatus Sholikhah; Winnuly Winnuly (Jurnal Konseling Pendidikan Islam, 2026)
This study examines the Take and Give strategy as a character education model for mitigating mild bullying indicators in early childhood at TK Aisyiyah Bustanul Athfal Tegalrejo. Grounded in Lickona's character education theory and Vygotsky's sociocultural perspective, the research addresses the gap between institutional character values and children's developing social behaviors. Using a qualitative descriptive approach, data were collected through interviews with the principal and teacher, direct classroom observations, and document analysis. Findings reveal that mild bullying manifestations—such as teasing, reluctance to share, and object-snatching—reflect children's social-emotional developmental challenges rather than intentional aggression. The Take and Give strategy, implemented through structured peer exchanges of cards, objects, and information, effectively cultivates prosocial behaviors including sharing, cooperation, empathy, and respectful communication. Children demonstrated increased willingness to share, enhanced peer interaction, and reduced tendencies toward teasing following strategy implementation. Success factors include institutional alignment with character education goals, consistent teacher scaffolding, and integration within the school's cultural framework. While some children require continued individualized support, the strategy offers a simple, cost-effective, and contextually grounded approach for fostering positive social development. This study contributes to early childhood character education research by repositioning Take and Give from an active learning technique to a pedagogical instrument for bullying prevention through repeated, meaningful social experiences.